Answer:15x+7
Step-by-step explanation:
First you would see that the -(-10x+6) would turn into 10x+6 meaning that the whole equation would turn into 5x+1+10x+6. Then add the x numbers together and the whole numbers separate. So now your answer should be 15x+7
Answer:
C=84
Step-by-step explanation:
Since you use 3 for pi. You plug the radius into the formula. C=2×3x14=84
Answer:
15.60 times 100 divided by 390=4%
Step-by-step explanation:
Answer:
A. f(x) = x^2 + 4x + 3
D. f(x) = -2x^2 - 8x + 1
Step-by-step explanation:
The axis of symmetry is found by h = -b/2a where ax^2 +bx +c
A. f(x) = x^2 + 4x + 3
h = -4/2*1 = -2 x=-2
B. f(x) = x^2 - 4x - 5
h = - -4/2*1 = 4/2 =2 x=2 not -2
C. f(x) = x^2 + 6x + 2
h = -6/2*1 = -3/2 = x=-3/2 not -2
D. f(x) = -2x^2 - 8x + 1
h = - -8/2*-2 = 8/-4 =-2 x=-2
E. f(x) = -2x^2 + 8x - 2
h = - 8/2*-2 = -8/-4 =2 x=2 not -2
Answer:
(5r - 20)
Step-by-step explanation:
(3r + 14) + (Ar + B) = (8r - 6)
B = -6 - 14 = -20
A = 8 - 3 = 5